14N–1H HMQC solid-state NMR as a powerful tool to study amorphous formulations – an exemplary study of paclitaxel loaded polymer micelles. Issue 31 (17th June 2020) - Grüne, Marvin; Luxenhofer, Robert; Iuga, Dinu; Brown, Steven P.; Pöppler, Ann-Christin
Abstract : 14 N– 1 H HMQC experiments are powerful experiments to characterize amorphous drug–polymer formulations of paclitaxel yielding well-separated signals in the 14 N dimension as well as information on the symmetry of 14 N and 14 N– 1 H interactions. Abstract : Amorphous drug–polymer formulations are complex materials and often challenging to characterize, even more so if the small molecule component itself is increasingly complex. In this work, we present 14 N– 1 H HMQC magic-angle spinning (MAS) NMR experiments in the solid state as a promising tool to study amorphous formulations. Poly(2-oxazoline) based polymer micelles loaded with different amounts of the cancer drug paclitaxel serve to highlight the possibilities offered by these experiments: while the dense core of these polymeric micelles prevents NMR spectroscopic analysis in solution and the very similar 15 N chemical shifts hamper a solid-state NMR characterization based on this nucleus, 14 N is a very versatile alternative. 14 N– 1 H HMQC experiments yield well-separated signals, which are spread over a large ppm range, and provide information on the symmetry of the nitrogen environment and probe 14 N– 1 H through-space proximities. In this way, the overall complexity can be narrowed down to specific N-containing environments. The results from the experiments presented here represent a valuable puzzle piece, which helps to improve the structural understanding of drug–polymer formulations. It can be straightforwardly combined with complementary NMR spectroscopic experiments and other analytical techniques.